2012
DOI: 10.1021/cn3001203
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Modulates α-Synuclein Aggregation and Toxicity

Abstract: In human beings, Parkinson's disease (PD) is associated with the oligomerization and amyloid formation of α-synuclein (α-Syn). The polyphenolic Asian food ingredient curcumin has proven to be effective against a wide range of human diseases including cancers and neurological disorders. While curcumin has been shown to significantly reduce cell toxicity of α-Syn aggregates, its mechanism of action remains unexplored. Here, using a series of biophysical techniques, we demonstrate that curcumin reduces toxicity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
244
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 275 publications
(254 citation statements)
references
References 79 publications
7
244
1
Order By: Relevance
“…␣-Synuclein (␣-Syn) protein was expressed and purified according to the protocol described by Volles and Lansbury (38) in E. coli BL21 (DE3) strain. For ␣-Syn, 30 mg/ml lyophilized protein was dissolved in 20 mM MES buffer, pH 6.0, and low molecular weight ␣-Syn was prepared by passing the dissolved protein through 100 kDa cut-off membrane as described before (39). The Eppendorf tubes containing peptide/protein solutions were placed into an EchoTherm model RT11 rotating mixture (Torrey Pines Scientific) at 50 rpm inside a 37°C incubator.…”
Section: Methodsmentioning
confidence: 99%
“…␣-Synuclein (␣-Syn) protein was expressed and purified according to the protocol described by Volles and Lansbury (38) in E. coli BL21 (DE3) strain. For ␣-Syn, 30 mg/ml lyophilized protein was dissolved in 20 mM MES buffer, pH 6.0, and low molecular weight ␣-Syn was prepared by passing the dissolved protein through 100 kDa cut-off membrane as described before (39). The Eppendorf tubes containing peptide/protein solutions were placed into an EchoTherm model RT11 rotating mixture (Torrey Pines Scientific) at 50 rpm inside a 37°C incubator.…”
Section: Methodsmentioning
confidence: 99%
“…In one condition, phosphate buffer was placed on top of the gel surface (condition A) and incubated for up to 21 days. To mimic the possible degradation of the gel in vivo, the gel was mixed with 3.8 μg ml − 1 proteinase K (the enzyme most frequently used for the nonspecific degradation of protein and amyloids 23,24 ) and incubated for 21 days. After 7 and 21 days of incubation, 150 μl of soluble α-Syn was mixed with 3 μl solution of phosphate buffer placed on the top (condition A) to achieve a 2% v/v concentration of degraded gel.…”
Section: Protein Expression and Purification And Aggregation Kineticsmentioning
confidence: 99%
“…In one condition, phosphate buffer was placed on top of the gel surface (condition A), and the gel was then incubated up to 21 days. To mimic the degradation of the gel in vivo, the gel was further mixed with 3.8 μg ml − 1 proteinase K, an enzyme most frequently used for the non-specific degradation of proteins and amyloids 23,24 (condition B), and incubated for 21 days. After 7 and 21 days of incubation, 2% v/v degraded gel products from both conditions A and B were added to WT α-Syn, and aggregation was monitored via ThT fluorescence (Figures 3c and d).…”
Section: Toxicity and Seeding Capacity Of Amyloid Hydrogelsmentioning
confidence: 99%
“…Curcumin, a phenolic compound from the Asian spice turmeric (Curcuma longa), is of great interest for its plausible role in countering neurodegenerative diseases like Parkinson disease (1-3) and Alzheimer disease (AD) 3 (4,5). In vitro studies have shown that curcumin can retard the process of amyloid ␤ (A␤) aggregation (5,6), which is supposed to be the initiator of AD.…”
Section: ؉mentioning
confidence: 99%